Evolving Synthetic Data Generating Programs for Text Recognition Tasks - Evolving a Diverse Population of SyntheticData Generators using Genetic Programming with Novelty Search for Robust Text Recognition Models - Cooper, Daniel (2021)
Dissertation presented as partial requirement for obtaining the Master’s degree in Data Science and Advanced Analytics